Gendered Information Seeking and Community Health Communication for Stunting Prevention: Integrating Social Marketing, Nudging and Digital Engagement in Rural Indonesia - Netty Dyah Kurniasari; Iriani Ismail; Farida Nurul Rahmawati; Nikmah Suryandari; Iswari Hariastuti; Prita Dellia; Ana Tsalitsatun Ni'mah (Jogjakarta Communication Conference (JCC), 2026)
Stunting remains a persistent public health issue in rural Indonesia, driven not only by nutritional deficits but also by communication gaps and gendered dynamics in health information access. This study examines how gender influences information-seeking behaviour and how community-based health communication affects knowledge, attitudes, and practices (KAP) related to stunting prevention. Using a quantitative survey design, data were collected from mothers of toddlers in a rural village. The findings reveal that exposure to health communication significantly affects knowledge and attitudes, which subsequently influence healthy practices. However, access to information is uneven and shaped by gender roles, social structures, and media exposure. This study proposes an integrated model combining social marketing, nudging strategies, and digital engagement to strengthen community-based interventions. The findings contribute to health communication literature by emphasising gender-sensitive approaches and offering practical implications for designing scalable communication interventions in low resource settings.